Development of a UPLC-MS/MS method for the determination of lacosamide and its metabolite and its application to drug-drug interaction - Chen, Jie; Shen, Yuxin; Xia, Hailun; Chen, Xiaohai; Xu, Ren-Ai; Lin, Guanyang; Dai, Gexin (Frontiers in Pharmacology, 2023)
Lacosamide, a third-generation novel antiepileptic drug, was first approved in 2008 as an adjunct to partial seizures. In 2014, the U.S. Food and Drug Administration (FDA) approved it as a single agent for partial seizures. Since epilepsy is a chronic condition, most patients need long-term antiepileptic medicinal products, so it is even more important to consider the drug-drug interactions (DDIs). For the purpose of this experiment, an ultra performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) assay with accuracy and simplicity was optimized and fully validated for the simultaneous quantitative determination of lacosamide and O-Desmethyl-lacosamide (ODL), and DDIs between lacosamide and nisoldipine in vivo and in vitro was researched. The protein was precipitated with acetonitrile, the analytes were eluted with acetonitrile and a 0.1% formic acid solution in a gradient program, and lacosamide, ODL, and lamotrigine (Internal Standard, IS) were successfully separated by chromatography. The findings of the biological analysis revealed that the lower limit of quantification (LLOQ) for lacosamide in samples was 2 ng/mL and the linearity ranged from 2-10000 ng/mL. The LLOQ for ODL was 1 ng/mL, while the linearity range for this substance was 1-1000 ng/mL. In rat liver microsomes (RLM), the LLOQ of ODL was 80 ng/mL and the linear range was 80-40000 ng/mL. The selectivity, stability, matrix effect and recovery rate were all satisfied with the need of quantitative analysis of samples. Then, the UPLC-MS/MS assay was employed successfully on the interactions of lacosamide and nisoldipine in vivo and in vitro. The half-maximal inhibitory concentration (IC50) was 3.412 μM in RLM, where nisoldipine inhibited the metabolism of lacosamide with a mixture of inhibition mechanism. In rat pharmacokinetic experiments, it was found that nisoldipine could significantly change the pharmacokinetic characteristics of lacosamide, including AUC(0-t), AUC(0-∞), Tmax, CLz/F and Cmax, but had no significant effect on ODL. In summary, the UPLC-MS/MS method could accurately and sensitively quantify lacosamide and ODL, and could be used for the interaction between nisoldipine and lacosamide in vivo and in vitro.